THE MAIN DIFFICULTIES IN LEARNING A NEW LANGUAGE - Djalolov, Furqat (Журнал иностранных языков и лингвистики, 2021)
This article deals withforemostdifficulty in mastering a foreign language and teaches how toincrease the foreign language materials gradually that we are exposed.